Taking trade to the streets : the lost history of public efforts to shape globalization - Aaronson, Susan A. (Ann Arbor : University of Michigan Press, 2001)
Examines the history of trade agreement critics, focusing particular attention on the North American Free Trade Agreement [NAFTA] between Canada, Mexico, and the United States and the Tokyo and Uruguay Rounds of trade liberalization under the General Agreement on Tariffs and Trade [GATT]. [preface].
Chapter 6: Gleaning the GATTChapter 7: Thinking Locally, Acting Globally -- Notes -- Bibliography -- Index
Includes bibliographical references (pages 237-252) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: North American Free Trade Agreement -- (1992 December 17); General Agreement on Tariffs and Trade (Organization); World Trade Organization; Canada. -- (1992 oct. 7); Accord général sur les tarifs douaniers et le commerce (Organisation); Organisation mondiale du commerce; General Agreement on Tariffs and Trade (Organization); World Trade Organization; North American Free Trade Agreement (1992 December 17); Canada. -- 1992 Oct. 7; General Agreement on Tariffs and Trade (Organization); World Trade Organization; Accord général sur les tarifs douaniers et le commerce; Organisation mondiale du commerce; Free trade; Foreign trade regulation; Globalization; Free trade -- United States; United States -- Commercial policy; Libre-échange.; États-Unis -- Politique commerciale; Commerce international -- Réglementation.; Mondialisation; Libre-échange -- États-Unis.; globalism; BUSINESS & ECONOMICS -- International -- Marketing; POLITICAL SCIENCE -- International Relations -- Trade & Tariffs; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- Exports & Imports; POLITICAL SCIENCE -- Public Policy -- Economic Policy; Commercial policy; Foreign trade regulation; Free trade; Globalization; United States; Außenhandelspolitik; Globalisierung; Protestbewegung; Freihandelsabkommen; free trade; trade agreement; trade liberalization; globalization; social implication; history; protectionism; trade policy; trade negotiation; GATT; NAFTA; labour standards; environmental protection; consumer behaviour; nongovernmental organization; Canada; USA; Free trade; Foreign trade regulation; Globalization; Free trade -- United States